2020
DOI: 10.1200/jco.2020.38.15_suppl.e19048
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress, social function and financial burden of cancer patients receiving treatment in an African setting.

Abstract: e19048 Background: The improvement in the quality of cancer treatment is key to increasing survival. However, the functional well-being of these patients is equally important. This study aimed to assess the degree of psychological distress, social function and financial burden in patients undergoing cancer treatment in our center. Methods: A cross-sectional study was designed to prospectively recruit patients in our teaching hospital between December 2019 to February 2020. Those with cancer, aged 18 years and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…[21][22][23]32,[35][36][37] In our study, ECOG performance status was the only factor associated with distress similar to what a Nigerian study showed. [22] Other studies have reported being female, type of malignancy, being on chemotherapy, or under palliative care as independent predictors of distress. [15,32,35,37] The problem list identified transportation as a major problem under the practical problem domain.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…[21][22][23]32,[35][36][37] In our study, ECOG performance status was the only factor associated with distress similar to what a Nigerian study showed. [22] Other studies have reported being female, type of malignancy, being on chemotherapy, or under palliative care as independent predictors of distress. [15,32,35,37] The problem list identified transportation as a major problem under the practical problem domain.…”
Section: Discussionsupporting
confidence: 89%
“…[21,23] The mean distress score in our patients was similar to that in other studies with a range of 2.47-4.7 but much lower than that in studies conducted in palliative settings where more than 70% of patients had high levels of distress. [21][22][23]32,[35][36][37] In our study, ECOG performance status was the only factor associated with distress similar to what a Nigerian study showed. [22] Other studies have reported being female, type of malignancy, being on chemotherapy, or under palliative care as independent predictors of distress.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In some developed countries in Europe and the United States, medical social workers have become a mature and specialized profession to intervene in the medical process of patients in the whole process, and their education and training system is sound ( 1 ). Patients with cancer face the threat of long course of the disease, treatment cycle, and even death, which destroys their mental health and social function ( 2 , 3 ). Therefore, they need social work services as part of holistic care and health management.…”
Section: Introductionmentioning
confidence: 99%